Culture and foreign language education : insights from research and implications for the practice - Chan, Wai Meng, 1962-; Bhatt, Sunil Kumar; Nagami, Masanori; Walker, Izumi (Studies in second and foreign language education, 2015)
"This book offers insights from current research on the role of culture in foreign language learning as well as the construction of culture and identity through language learning and use. It presents original empirical studies and theoretical discussions which bear important implications for curricular practice in language education, as well as accounts of developmental projects for integrated foreign language and culture learning"--Provided by publisher